The knowledge of early education schoolgirls about teaching aids used in physical education classes - Grażyna Kosiba; Janusz Jaworski; Eligiusz Madejski; Adrian Gądek (University of Applied Sciences in Tarnow, Poland, 2017)
Introduction: Apart from knowledge, teaching aids also play a major role in teaching and improving motor skills, particularly in early school education. They not only facilitate the implementation of the teaching process but also trigger and reinforce educational activity. Aim of the study: The aim of the presented research was to establish the state of knowledge of primary education schoolgirls, grade 1-3, about the sport equipment that should be used in physical education classes and various sport disciplines. Material and methods: The research had a continuous character and covered a group of 267 girls aged 7 to 9. The schoolgirls came from randomly selected village schools in the neighbourhood of Krakow. Results: As the results of the research show the state of knowledge of the schoolgirls about the basic teaching aids used in physical education classes can be generally recognized as average. What the surveyed schoolgirls found most difficult was providing correct names for such equipment as: a badminton racket, gym stick, gym hoop and ringo. Among all the teaching aids illustrated in the test, the surveyed best recognized balls used in team games (football, volleyball and basketball). In this case as many as 93% of 9 year old girls answered correctly. Conclusions: Generally, in all analysed questions the research results show a statistically significant (level p ≤ 0.05) improvement of the girls' knowledge on tools and equipment used for work out with increasing age.